Atrial Fibrillation and SCN5A Variants - Savio-Galimberti, Eleonora (Card Electrophysiol Clin, 2014)
Although atrial fibrillation (AF) is clinically and genetically a highly heterogeneous disease, recent studies suggest that the arrhythmia may arise because of interactions between genetic and acquired risk factors – the so called “double-hit” hypothesis. Genome-wide association studies have identified common AF susceptibility loci, and linkage analysis and candidate gene approaches have identified mutations in genes that encode for cardiac ion channels and signaling proteins; however, most of the heritability of AF still remains unexplained. The voltage-dependent cardiac sodium channel, encoded by SCN5A, conducts the main cardiac inward sodium current (I(Na)) and is responsible for the upstroke of the atrial action potential. Mutations in SCN5A, which encodes the α-subunit of the Na(V)1.5 channel, have been linked with increased susceptibility to not only AF but also ventricular arrhythmias (long QT syndrome, Brugada syndrome), progressive cardiac conduction disease, and overlap syndromes with mixed arrhythmia phenotypes. Over the last decade, functional characterization of SCN5A mutations by expressing the channel in heterologous expression systems and applying cellular electrophysiological techniques has not only advanced our understanding of molecular mechanisms of AF but also potentially identified a mechanism-based approach to treating this common and morbid condition.